El aprendizaje basado en proyectos (abp) y su incidencia en el aprendizaje de la asignatura emprendimiento y gestión de los estudiantes de tercer año de bachillerato general unificado en la Unidad Educativa Colimes, cantón colimes, periodo lectivo 2022-2023 - Soledispa Piza, Rosendo Aníbal (2024)
The objective of this project “Project-Based Learning and its impact on the learning of the subject Entrepreneurship and Management of Third Year students of the Unified General Baccalaureate in the Colimes Educational Unit, Colimes canton, school year 2022-2023” : Analyze this didactic strategy and its impact on the learning process of the subject of Entrepreneurship and Management of the Third-year students of the Unified General Baccalaureate at the Colimes Educational Unit, to achieve the development of entrepreneurial cognitive skills. The methodology that was applied in this project is of a quantitative-qualitative level, so information was collected to be analyzed with tables and graphs, the bibliographic part allowed a better understanding of the conceptual and theoretical contents of the project, through different authors and to reinforce the research results; The methods used were deductive, inductive, and analysis and synthesis. The field work was determined by pertinent observation to collect timely information. In addition, an interview with the manager and surveys were applied to students, teachers, and students. Finally, an alternative proposal was developed as an essential part of the solution to the problem, by implementing a teacher training plan on Project-Based Learning, with the purpose of innovating teacher actions in their professional training and providing students with better development. of skills for business implementation based on real cases.